Spontaneous Erythroid Leukemia in a 7-Week-Old Crl:CD (SD) Rat - Yamamoto, Emi (The Japanese Society of Toxicologic Pathology, 2010)
A young male Crl:CD (SD) rat with erythroid leukemia that presented with emaciation, abdominal distension and a pale visible mucosal membrane was euthanized at 7 weeks of age. At necropsy, enlargement of liver, spleen and pancreatic lymph node was noted. Analysis of blood smear samples revealed many mono- or binucleated erythroblasts that had PAS-positive vacuoles in the cytoplasm. Histopathologically, neoplastic proliferation of atypical cells was observed in the hepatic sinusoids, splenic red pulp, bone marrow, pancreatic lymph node, kidney and lung. Neoplastic cells showed a round to spindle shape, and some neoplastic cells had deeply stained small nuclei and small cytoplasms and resembled erythroblasts. Immunohistochemically, many neoplastic cells were positive for hemoglobin. To our knowledge, this is the first report of erythroid leukemia in a rat of this age. The observed features were similar to those of pure erythroid leukemia in humans.